Palatalization of Javanese Consonant Allophones Osing Dialect in Kendhang Kempulan Songs on The Album Lagu-Lagu Banyuwangi Ngetop Sumiyati - Irakusuma, Ratna Nur Fatimah; Winarti, Daru; Salahuddin, Salahuddin (Jayapangus Press, 2025)
The people of Osing, Banyuwangi, have unique consonant allophones in their speech. Still a dialect of Javanese, the realization of the phoneme of the Osing dialect shows significant differences with the standard variety of Javanese. In the Osing dialect, there are a number of consonant phonemes which in reality are pronounced with a y sound with the meaning of the word that does not change even if the y sound is omitted. Against the background of these problems, this study aims to identify the palatalization of the consonant allophone of the Javanese Osing dialect. Data was collected from kendhang kempulan songs in the album